PENGEMBANGAN E-LKPD BERBASIS PENDEKATAN KONTEKSTUAL MENGGUNAKAN LIVEWORKSHEETS PADA MATERI BANGUN RUANG SISI DATAR KELAS VIII - Siti Maftuchatul Izzah; Nanang Nabhar Fakhri Auliya (Adisam Publisher, 2024)
This study aims to produce teaching materials in the form of E-LKPD based on a contextual approach using liveworksheets on class VIII flat sided building materials. As well as to analyze the feasibility of E-LKPD based on a contextual approach using liveworksheets on class VIII flat sided building material. This type of research is Research and Development (R&D). Research and Development is a step that aims to develop new products or improve existing products so that they can be accounted for. The research and development model used is the ADDIE model. The ADDIE Model stands for Analyze, Design, Development, Implementation, and Evaluation. The data collection instruments in this study were material expert validation sheets, media expert validation sheets, and student response assessment sheets. The validation results from material experts get an average score of 88, so that the material included is in the very feasible category. While the validation results from media experts get an average score of 85.5, so it is also included in the very decent category. In product trials, the subjects of this study were students of class VIII MTs. NU Ma'rifatul Ulum Mijen Kaliwungu Kudus totaling 50 students divided into small- scale trials followed by 15 students with an average score of 85.5 and large-scale trials attended by 35 students with an average score of 86.3 . Thus the two trials are included in the very feasible category. So it can be concluded that the E-LKPD Based on a Contextual Approach Using Liveworksheets on Building Materials for Class VIII Flat Sided Spaces can be said to be feasible and can be used to support the learning process.